Synthesis and reactivity of bioinspired superoxocopper(II) complexes - Laxmi, Shoba (Nanyang Technological University, 2022)
End-on superoxocopper(II) are evidenced to be active oxidants in a number of copper-containing oxygenase enzymes which are responsible for catalysing the stereoselective oxidation of moderate strength C─H bonds at ambient temperatures. Presently, there are over twenty synthetic biomimetic end-on superoxocopper(II) complexes which have played an invaluable role in understanding the factors that govern dioxygen activation and substrate reaction mechanisms. However, most of them are only stable at cryogenic temperatures and exhibit limited reactivity with exogenous substrates. The England group recently reported three end-on superoxocopper(II) complexes, [CuII(η1-O2•−)(Ar3-TMPA)]+ (Ar = tpb, dpb and dtbpb), that are fully stable against dimerization at all temperatures. However, the reactivity of these [CuII(η1-O2•−)(Ar3-TMPA)]+ complexes was found to be sluggish attributed to steric hindrance. This study aims to produce more reactive derivatives of these complexes, by reducing their steric bulk, whilst also addressing some deficiencies in the existing Ar3-TMPA work.